2022
DOI: 10.5194/essd-14-651-2022
|View full text |Cite
|
Sign up to set email alerts
|

A global seamless 1 km resolution daily land surface temperature dataset (2003–2020)

Abstract: Abstract. Land surface temperature (LST) is one of the most important and widely used parameters for studying land surface processes. Moderate Resolution Imaging Spectroradiometer (MODIS) LST products (e.g., MOD11A1 and MYD11A1) can provide this information with moderate spatiotemporal resolution with global coverage. However, the applications of these data are hampered because of missing values caused by factors such as cloud contamination, indicating the necessity to produce a seamless global MODIS-like LST … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…7) and overcast weather (days 219 and 293 in Fig. 7) (Zhang et al, 2022a), the gridded Ta can illustrate the UHI phenomenon. An existing study has found that the estimated Ta in urban areas 210 was more accurate than those of other regions (Zhang et al, 2022b), specifically suggesting its great value for urban applications.…”
Section: Spatial and Temporal Patterns Of Tamentioning
confidence: 99%
“…7) and overcast weather (days 219 and 293 in Fig. 7) (Zhang et al, 2022a), the gridded Ta can illustrate the UHI phenomenon. An existing study has found that the estimated Ta in urban areas 210 was more accurate than those of other regions (Zhang et al, 2022b), specifically suggesting its great value for urban applications.…”
Section: Spatial and Temporal Patterns Of Tamentioning
confidence: 99%
“…In this study, eight variables reflecting the changes and spatial distribution characteristics of temperature were 170 used to predict human thermal indices (Table 1) in addition to the meteorological variables. As LST is one of the most essential parameters for predicting human thermal indices, the seamless LST dataset created by Zhang et al (2022b) The spatial resolution of this dataset is 3″ (i.e., ~90 meters at the equator). In addition, the slope was also extracted from the elevation data to act as the topography predictor.…”
Section: Covariatesmentioning
confidence: 99%
“…Limited is high-resolution multiple human thermal stress indices dataset, compared with extensive studies in producing land surface temperature (LST) or near surface air temperatures (SAT). In particular, 100 numerous LST datasets, such as Land Surface Temperature in China (LSTC) (Zhao et al, 2020) and the global seamless land surface temperature dataset (Zhang et al, 2022b;Hong et al, 2022), and near surface air temperature datasets such as ERA5 (ECMWF, 2017), TerraClimate (Abatzoglou et al, 2018), and GPRChinaTemp1km (He et al, 2021) have been produced. Few coarse-resolution human thermal stress datasets have been produced, such as ERA5-HEAT (Di Napoli et al, 2020), 105 HDI_0p25_1970_2018 (hereafter, HDI) (Mistry, 2020), andHiTiSEA (Yan et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of models and algorithms have been proposed to improve existing satellite observations or develop new indicators for monitoring urban environment. For example, with the advance of these methods, the gap-filled seamless data of land surface temperature and aerosol optical depth have been developed (Zhang et al 2022 ; Li et al 2020b ), and derived products from satellite observations such as phenology indicators with high spatial resolutions in urban areas are emerging (Li et al 2019 ). These improved products in terms of coverage or spatial resolution serve as important and complementary information to understand urban environment.…”
Section: Monitoring Urban Environment and Its Dynamicsmentioning
confidence: 99%